Avaliação da incorporação dos conceitos de sustentabilidade no projeto de habitações de interesse social : o caso Loteamento Santa Maria do Limão, Aracruz, ES - Gomes, Daniella Amorim (2017)
The study presents analyzes aimed at the production of Social Interest Housing in the context of a chosen study object, theSanta Maria do Limão Allocation, located in the Municipality of Aracruz, ES. The methods of analysis are based on the methodology of Post-occupation Evaluation, Energy-Environmental Assessment of Materials and on the evaluation of the quantity ofconstruction and demolition waste. The APO has its own methods and techniques in order to systematically evaluate the built environment, with a view to technical, cognitive, functional and cultural aspects, mainly through the evaluation of the resident tohisdwelling. The Energy-Environmental Assessment of Materials, demonstrates the environmental energy impacts caused by the Civil Construction Sector, which despite being a significant sector for the economic and social growth of the country, is characterized by the environmental degradation caused mainly by the production of its building materials. The estimation of the amount of waste produced by the housing of the case study, are related to the questions related to the APOand the Environmental-Energy Assessment of the Materials. Through the APO, it obtained an overview of the inadequacies of the dwellings and the changes made, being possible to quantify them in the volume of residues produced and to evaluate the energy-environmental expenses of these modifications. After analysis in theAllocation, it was possible to propose guidelines and interventions in the current production patterns, through a Project of Housing of Expansible Social Interest. The results point to the need to review the production patterns of HIS currently practiced, considering several factors at the design stage, such as the opinion of the future residents of the dwellings, the choice of the correct architectural party for each situation in order to eliminate standardization And constant repetition of the models, and especially to use criteria of sustainability in the choice of materials and constructive technologies.